Detection of Streptococcus bovis from hospitalised patients with inflammatory bowel disease - Aziz, Zainal Shukri@Abdul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
This final year research project is about the detection of Streptococcus bovis (S. bovis) in hospitalized patients that suffers from inflammatory bowel disease or colonic carcinoma. From 50 samples collected from patients, one have been positively identified for S.bovis. From Chisquare analysis, it has been determined that there is no significant association between the presence of Streptococcus bovis species and the age, sex and the type of disease of hospitalized patients at HUSM. There is possible association between the race of patients and presence of the bacteri . Several factors regarding patients conditio~ validity of the sample and collecting and processing method have been identify as reasons why such results have been achieved.